Recent Progress in the Simulation of Chiral Systems with Real Time Propagation Methods. Issue 12 (27th October 2021) - Mattiat, Johann; Luber, Sandra
Abstract: In this brief review, an overview about recent efforts to simulate the spectroscopic signatures of chiral molecules is given with focus on real time propagation approaches to solve the time‐dependent Schrödinger equation. In particular the simulation of electric circular dichroism spectra and vibrational Raman optical activity is discussed. In comparison to linear absorption spectra, where only the response of the electric dipole moment is necessary, the response of the magnetic dipole moment and electric quadrupole moment is more intricate. Issues such as gauge origin dependence, basis set dependence, non‐local potentials and the dipole approximation are addressed. Abstract :